The impact of between analytical platform variability on the classification of pleural effusions into exudate or transudate using Light's criteria. Issue 7 (16th February 2017) - Cornes, Michael P; Chadburn, Andrew J; Thomas, Claire; Darby, Catherine; Webster, Rachel; Ford, Clare; Gama, Rousseau
Abstract : Background: Light's criteria are ratios of pleural fluid to serum total protein (TP), pleural fluid to serum lactate dehydrogenase (LDH) and pleural fluid LDH to the upper reference limit for serum LDH. They are used to classify pleural effusions into an exudate or transudate when pleural fluid protein is 25–35 g/L. We evaluated the impact of between analytical platforms on the classification of pleural effusions using Light's criteria. Methods: Light's criteria were used to classify pleural effusions with fluid TP between 25 and 35 g/L into exudate and transudate. LDH and TP were analysed using an Abbott ARCHITECT c16000 analyser using a lactate to pyruvate method for LDH and two Roche Cobas 800 c702 analysers, one using a lactate to pyruvate method (laboratory B) and one a lactate to pyruvate method (laboratory C). Results: Eighty-three paired serum and pleural fluid samples were analysed. Of these, 44 samples had a pleural fluid TP between 25 and 35 g/L and were classified according to Light's criteria. Classification of pleural fluid into transudate or exudate using different analytical platforms was 82% concordant. The LDH ratio and TP ratio were similar in laboratory B and laboratory C, but these were respectively lower (p<0.001) and higher (p<0.001) than those at laboratory A. Conclusions: Although Light's criteria are ratios, which should minimise interassay variability, we report 18% discordance between different analytical platforms. The discordance was largely due to the performance of LDH and to a lesser extent protein assays in pleural fluid. Laboratories should be aware that assays may perform differently in serum and pleural fluid.